Pengawetan Jenis - Jenis Bambu Sebagai Bahan Konstruksi Bangunan Arsitektur - Dewa Gede Bayu Pradana Putra; I Made Bagus Basunjaya; I Komang Mulyadi Arisasmika; Made Mas Surya Wiguna; Ni Wayan Meidayanti Mustika (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
Bamboo has different durability based on the type and method of preservation. This research was conducted to determine the method of preservation of the types of bamboo used as architectural building construction materials starting from before processing and after construction was built. The research method used is descriptive qualitative method which includes data collection on the types of bamboo used in the construction of architectural buildings and bamboo preservation methods. From the data collection, there are several types of bamboo that can be used as architectural building construction materials with different preservation methods on each bamboo before processing, namely preservation with petung bamboo using the Boucherie method, in wulung bamboo using a process that is preserved by diffusion with preservatives. continue, on the bamboo rope using the process of immersion with liquid alcohol, on the bamboo betung using the process of boiling in a drum tub. In addition, there is also a preservation process after the construction material is processed and built, namely by smoothing the surface of the bamboo with sandpaper then applying a chemical liquid in the form of bayclin and finally the bamboo is sprayed with varnish. By providing preservation of bamboo material, the durability of a bamboo architectural building can reach 10 - 20 years.